Phytomass production and micronutrient cycling by cover crops in the Brazilian cerrado of Goias. - Pacheco, Leandro Pereira; Fonseca, Weverson Lima; Menezes, Carlos César Evangelista de; Leandro, Wilson Mozena; Assis, Renato Lara de; Petter, Fabiano André; Petter, Fabiano André (Comunicata Scientiae, 2018)
The objective of this work was to evaluate the performance of cover crops over the phytomass production, accumulation and release of micronutrients in the Brazilian Cerrado of Goiás. The experiment was performed in Rio Verde, GO, Brazil, installed in dystroferric red latossol, from April 2008 to April 2009. The experimental design was a randomized block, in a factorial scheme (4x6), by split-splot array, with four replications. The plots received the cover crops, and the sub-plots consisted by biomass evaluations in six different times. The evaluated cover crops were: Urochloa ruziziensis, Pennisetum glaucum and U. ruziziensis + Cajanus Cajan and fallow area as reference. For the assessment of accumulation and release of biomass and micronutrients, biomass samples were collected in six times, from the management desiccation of the cover crops at the final off-season. The species U. ruziziensis and U. ruziziensis + C. cajan stood out in accumulation and in the release of biomass and micronutrients in the Brazilian Cerrado of Goiás.